Point defects in oxide and nitride semiconductors - Stehr, Jan Eric; Justus Liebig University Giessen (My University, 2011)
In this thesis the material systems zinc oxide, aluminum nitride and gallium oxide were investigated by electron paramagnetic resonance and optical spectroscopy in order to gain insight into the point defects in these materials which are affecting the optical and electrical properties.For a long time doping with nitrogen was thought to be the best possibility to create p-type conducting ZnO. However, recently there were doubts whether nitrogen forms a shallow acceptor or not. That acceptor level and the corresponding photo-transition process were characterized by EPR and photo-EPR. The photo-transition process charging the nitrogen acceptor from the negative charged non-paramagnetic state into the neutral paramagnetic, was found to be a direct process to the conduction band with an optical ionization energy Eopt = 2.1 eV. Therefore, it was proven, that the defect caused by a nitrogen atom substituting an oxygen atom in ZnO, forms a deep acceptor level.The characterization of aluminum nitride bulk crystals by EPR reveals two defects, a donor and an acceptor. The donor which originates most likely from an oxygen atom substituting a nitrogen atom has a negative U-behavior and forms a DX- center. The optical ionization energy of the DX- center was determined to 1.9 eV and the formation energy was estimated to 3 meV. A (V_{Al}-O_N) defect complex is most likely the origin of the acceptor observed in the EPR measurements. The presence of (V_{Al}) and (O_N) is confirmed by optical spectroscopy and further the formation of (V_{Al}-O_N) defect complexes is thermodynamically favored over the isolated defects. The energy level position is estimated to be 1.1 eV to 3.5 eV above the valence band.Transition metal ions are often incorporated in semiconductors as residual impurities and form deep level defects. In the case of gallium oxide two 3d transitions metals could be identified by EPR. Co2+ with a 3d7 electron configuration, located at an octahedral gallium lattice site, could be identified in bulk crystals due to its strong anisotropic g-values and its hyperfine interaction. In beta-Ga2O3 powder Cu2+ with a 3d9 electron configuration, the isotopes 63Cu (69.2 % natural abundance) and 65Cu (30.8 % natural abundance), located on an octahedral gallium site, could be identified.

In dieser Dissertation wurden die Materialsysteme Zinkoxid, Aluminiumnitrid und Galliumoxid mit Elektronenspinresonanz (ESR) und optischer Spektroskopie untersucht um mehr Informationen über Punktdefekte in den Materialien zu erhalten, welche die optischen und elektrischen Eigenschaften stark beeinflussen. Lange Zeit galt Stickstoff als einer der aussichtsreichsten Kandidaten um p-leitendes ZnO herzustellen. Allerdings häuften sich in letzter Zeit Anzeichen dafür, dass Stickstoff keinen flachen Akzeptor in ZnO formt. Um dieses Verhalten zu überprüfen wurden die Energieniveauposition und der dazugehörige Photo-Prozess des Stickstoffzentrums in ZnO mittel ESR und Photo-ESR untersucht. Bei dem Photo-Prozess der das Stickstoffzentrum von seinem negativ geladenen und nicht paramagnetischen Zustand in den neutralen paramagnetischen Zustand umlädt handelt es sich um einen direkten Prozess zum Leitungsband mit einer optischen Ionisierungsenergie von 2,1 eV. Damit konnte endgültig bewiesen werden das es ich bei N_O in ZnO um einen tiefen Akzeptor handelt.Die ESR-Untersuchungen von AlN zeigen einen Donator und einen Akzeptor. Das Donatorsignal ist höchstwahrscheinlich auf ON mit einer negativen Korrelationsenergie zurückzuführen und formt ein DX--Zentrum mit einer optischen Ionisierungsenergie von 1,9 eV. Die Energiebarriere zwischen dem metastabilen O_N und dem DX^--Zentrum beträgt 3 meV. Der Ursprung des ESR-Akzeptorsignals ist höchstwahrscheinlich ein (V-{Al}-O_N) Defektkomplex. Die Existenz von (V_{Al}) und (O_N) ist durch Photolumineszenz- und Absorptions-Messungen bestätigt, außerdem ist die Bildung von (V_{Al}-O_N) Defektkomplexen thermodynamisch erstrebenswerter als das Vorhandensein der isolierten Störstellen. Die Energieniveauposition des Akzeptors befindet sich 1,1 eV bis 3,5 eV über dem Valenzband.Übergangsmetalle sind oft als Restverunreinigungen in Halbleitern vorhanden und bilden tiefe Störstellen. In Galliumoxid konnten mittels ESR zwei 3d-Übergangsmetalle identifiziert werden. Co^{2+} mit einer 3d^7 Elektronenkonfiguration, auf einem oktaedrischen Gallium-Gitterplatz, konnte in Galliumoxid Volumenkristallen durch seine stark anisotropen g-Werte und seine Hyperfeinaufspaltung identifiziert werden. In beta-Ga2O3 Pulver konnte Cu^{2+} mit einer 3d^9 Elektronenkonfiguration mit den Isotopen 63Cu (69.2 % Häufigkeit) und 65Cu (30.8 % Häufigkeit) auf einem oktaedrischen Gallium-Gitterplatz identifiziert werden.
Punktdefekte in oxidischen und nitridischen Halbleitern
Keywords: ESR; Defekte; AlN; ZnO; Ga2O3; epr; defects; AlN; ZnO; Ga2O3; ddc:530